Efficiency of Automated Viral RNA Purification for Pediatric Studies of Dengue and Zika in Hyperendemic Areas - Sandra L. Delgado; Piedad M. Perilla; Doris M. Salgado; María Clemencia Rojas; Carlos F. Narváez (Journal of Tropical Medicine)
The isolation of nucleic acids is a critical and limiting step for molecular assays, which prompted the arrival in Colombia of automated purification instruments during the SARS-CoV-2 pandemic. The local application of this technology in the study of tropical diseases, such as dengue and zika, is beginning to be tested. We evaluated the efficiency of the automated extraction of viral RNA for studies of pediatric dengue and zika. Clinical samples of children with dengue that were well characterized through RNA isolation by silica columns and serotype-specific nested RT-PCR (DENV-1 n = 7, DENV-2 n = 5, and negatives n = 8) in addition to 40 pediatric plasma samples spiked with ZIKV (strain PRVA BC59) and 209 from negative pre-epidemic children were analyzed. RNA from patients was extracted by two automated standard and high-throughput protocols on the KingFisher™ Flex instrument. The isolated RNA was evaluated for concentration and purity by spectrophotometry, for structural and functional integrity by electrophoresis and expression of the RNase P gene, and usefulness in serotype-specific DENV detection by conventional and real-time RT-PCR. For the evaluation of ZIKV RNA, the commercial TaqMan Triplex® assay was used, along with a well-tested in-house RT-qPCR assay. The concentration of RNA (5.2 vs. 7.5 ng/μL, P=0.03) and the number of integral bands (9 vs. 11) were higher with the high-throughput protocol. However, the number of specimens serotyped for DENV by RT-qPCR was comparable for both protocols. The cycle thresholds of the TaqMan Triplex® commercial kit and the in-house assay for the detection of plasma ZIKV RNA isolated with the standard protocol showed a strong association (r = 0.93, P<0.0001) and a Cohen Kappa index of 0.98 when all 249 samples were analyzed. These preliminary results suggest that automated instruments could be used in studies of cocirculating flaviviruses that have represented a public health problem in recent decades in Colombia. They boast advantages such as efficiency, precision, time savings, and lower risk of cross-contamination.